Studi Komparasi Strategi Group Investigation (GI) dengan Student Team-Achievement Division (STAD) Terhadap Hasil Belajar IPA Siswa Kelas IV SD Muhammadiyah Terpadu Masaran Tahun 2015/2016". - Mayasari, Yunita Linda (2016)
This research into the background, namely that the class IV SDMT Masaran, learning process, especially the IPA still using media monotonous, so that students feel bored and have an impact on student learning outcomes Low. Students are able to receive a good science lesson with only 40 % and 60 % lower IPA student learning outcomes. This study aims to determine: (1) Differences influence strategies Group Investigation ( GI ) with Student Team - Achievement Division ( STAD ) the learning outcomes of Grade IV IPA SD Muhammadiyah Terpadu Masaran Year 2015/2016, (2) Which is greater influence between the Strategy Group Investigation (GI) with Student Team- Achievement Division (STAD) science to learning outcomes in the fourth grade students of SD Muhammadiyah Terpadu Masaran Year 2015/2016. This study was an experimental study. Subjects in this study were class IV Thoriq and IV Abdurrahman SD Muhammadiyah Terpadu Masaran Tahun 2015/2016. The data collection technique used is the technique of tests and documentation. Data analysis technique used is the t test prior to analysis prerequisite test is a test of balance and normality test. Based on the results of data analysis with a significance level of 5% obtained t > t table, namely 3,765 > 2,0017 with an average value of learning outcomes Thoriq fourth grade greater than grade IV Abdurrahman , is 86,50 > 76,33. The conclusion of this study are as follows : (1) There is a difference of influence Strategy Group Investigation (GI) with Student Team - Achievement Division (STAD) the learning outcomes IPA fourth grade students of SD Muhammadiyah Terpadu Masaran Tahun 2015/2016, (2) Strategy Group Investigation (GI) greater influence than strategy Student Team Achievement Division (STAD) the learning outcomes IPA fourth grade students of SD Muhammadiyah Terpadu Masaran Tahun 2015/2016 .